Book Review: Imperial Spheres and the Adriatic. Byzantium, the Carolingians and the Treaty of Aachen (812), ed. M. ANĈIĆ, J. SHEPARD and T. VEDRIŠ, London and New York: Routledge, Taylor & Francis Group, 2018 - TOUNTA, Eleni (Byzantina Symmeikta, 2019)
Book Review: Imperial Spheres and the Adriatic. Byzantium, the Carolingians and the Treaty of Aachen (812), ed. M. ANĈIĆ, J. SHEPARD and T. VEDRIŠ, London and New York: Routledge, Taylor & Francis Group, 2018